1979
DOI: 10.1111/j.2042-7158.1979.tb13502.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 5-hydroxytryptamine in blood platelets and its inhibition by drugs: role of plasma membrane and granular storage

Abstract: The initial uptake of 3H‐5‐hydroxytryptamine (3H‐5‐HT) showed linearity for short time intervals in normal and reserpinized blood platelets of guinea‐pigs, but was lower in reserpinized platelets. The Km values for the 3H‐5‐HT uptake were virtually identical in normal and reserpinized platelets, whereas Vmax was lower in the latter. Imipramine and chlorpromazine caused the same percentage inhibition of 3H‐5‐HT uptake in normal and reserpinized platelets; the reserpine‐like compound Ro 4–1284 inhibited the upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…3). As the K M of the initial uptake of 5-HT by platelets is probably determined by mechanisms at the plasma membrane [12], it may be suggested that alterations at the membrane could be responsible for the different uptake kinetics in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…3). As the K M of the initial uptake of 5-HT by platelets is probably determined by mechanisms at the plasma membrane [12], it may be suggested that alterations at the membrane could be responsible for the different uptake kinetics in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…(i) The high 5-HT concentration of the culture medium (0.1-1 AM) might downregulate both the rate of 5-HT uptake and the activity of tryptophan hydroxylase. Such an explanation has been put forward for platelets (50) and MTC cells (24). (ii) Based upon the homogeneity of the induced cell population, each 1C11* cell may contain a low number of functional carrier molecules compared to adult serotoninergic cells.…”
Section: Determination Of Cellular Content Of Bioactive Amines Andmentioning
confidence: 99%
“…In platelets incubated with imipramine (10-7 M), which completely blocks the uptake of 5-HT (Laubscher & Pletscher, 1979a) (Table 1).…”
Section: Imipraminementioning
confidence: 93%